The Influence of the Corona Virus Pandemic on Sustainable Development Goal 13 and United Nations Framework Convention on Climate Change Processes - Filho, Walter Leal; Hickmann, Thomas; Nagy, Gustavo J.; Pinho, Patricia; Sharifi, Ayyoob; Minhas, Aprajita; Islam, M Rezaul; Djalanti, Riyanti; García Vinuesa, Antonio; Abubakar, Ismaila Rimi (Frontiers in Environmental Science, 2022)
Apart from many social and economic problems worldwide, the COVID-19 pandemic has also led to a sudden halt in face-to-face climate-related meetings. Moreover, it has also negatively influenced the works related to the preparations for the 6th Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) and organizing the 26th Conference of the Parties of the UN Framework Convention on Climate Change (UNFCCC), namely COP26 to be held in Glasgow, which was postponed to November 2021. This article presents a global study undertaken among UNFCCC contact points and other climate experts, to ascertain the impacts of the pandemic on the implementation of SDG13 and UNFCCC processes. The methodological approach entails a bibliometric analysis, an online survey, and authors’ expert judgment. Results of the bibliometric analysis show that the most common terms associated with this theme are COVID-19, climate change, CO2, energy, "pandemic-related", and "adaptation-related". In addition, the survey revealed some difficulties associated with online participation in the processes from many developing countries. The study concluded that there is a negative impact of the COVID-19 pandemic on the UNFCCC process, more minor government priorities regarding climate action, loss of traction of the process, and a challenge to achieve the Paris Agreement, with less significant support from the respondents from less developed countries. The findings suggest that urgent action is needed, to make up for the lost time, and place climate issues more prominently on the global agenda.